Coupling of blasting seismographs to rock and its effectiveness for horizontal ground motion. (February 2017) - Segarra, P.; Sanchidrián, J.A.; Castedo, R.; del Castillo, I.
Abstract: In order to clarify the requirements for satisfactory coupling on rock, six methods to monitor vibrations with blasting seismographs are investigated in the longitudinal component of the vibratory motion. The methods studied consisted on placing the geophone mount on a granite surface freely (loosely), held with a sandbag, and attached with an anchor (the center of the geophone's mount was fixed with a plastic anchor, a bolt and a nut), thermal adhesive (glue), gypsum plaster (used as an adhesive) and double-sided tape. For each measuring condition, transmissibility in two mounts was assessed on a vibration shaker from 2 to 190 Hz at one or two vibration levels (5, 20 mm/s). The main findings of this work are: (1) Transmissibility varies with coupling method. It is flat at low frequencies and has a maximum at higher frequencies; in some trials mainly with anchored, glued and plastered such peak occurs outside the frequency range studied. (2) The frequency of the first maximum of transmissibility shifts towards smaller frequencies as the peak velocity increases when the bonding conditions are weak, as for free and sandbagged mounts. However, if the bonding is stiff enough, as for anchored or plastered mounts, transmissibility values at 5 and 20 mm/s are very similar. (3) The frequency of the first peak in the measured transmissibility provides a preliminary estimate of the performance of each method, so that its conditions of use should be defined upon frequency and velocity of the imposed motion, rather than using the anticipated peak acceleration, as it is currently made. These have been defined for the methods under study. (4) Anchoring and plastering provide the best performance, the later with smaller errors at high frequencies (>128 Hz). (5) The seismograph itself (not the coupling) is another source of error that should not be neglected specially for measurements in the low frequency range; large errors, exceeding by one order of magnitude those from coupling are obtained in the 2‒4 Hz band. Highlights: Six methods to couple blasting seismographs to rock are investigated. 100 tests were carried out on a vibration shaker under a horizontal motion. Guidelines to decide what coupling method should be used are provided. The best methods to couple the seismograph to rock are anchoring or plastering.